MEMBANGUN KARAKTER ANAK USIA DINI BERBASIS BUDAYA SEKOLAH USIA 4-5 TAHUN DI TKN BEIPOSO - Margareta Unde; Maria Anjelina Toyo; Selestiana Biba; Andi Nafsia (STKIP Subang, 2026)
Character refers to the traits, morals, and ethical values that distinguish one individual from another. Character development is not an instant process; it requires time, consistency, and a supportive environment. Like a solid building that needs a strong foundation, character must be nurtured from an early age. Therefore, instilling character in early childhood is essential, particularly through a school culture-based approach. This study aims to explore the development of character building among children aged 4-5 years at TKN Beiposo through the implementation of school cultural values. The data were collected using observation, interviews, and documentation techniques. The results indicate that character building in schools must be carried out through habituation, teacher modeling, and support from both school stakeholders and parents at home. The implementation of school culture in character education includes teaching children values such as discipline, honesty, responsibility, and mutual help. Thus, a consistently applied school culture can serve as an effective medium for developing strong character in early childhood